The last Christmas tree - Krensky, Stephen; Campion, Pascal (New York, N.Y. : Dial Books for Young Readers, 2014)
An eager little Christmas tree, not very tall or well-shaped, is the last on the lot but when it seems all hope of being covered with lights and ornaments is lost, a special person comes to take him home.
Keywords: Christmas trees -- Fiction; Hope -- Fiction